The Boston Tea Party - Freedman, Russell; Malone, Peter, 1953- (New York : Scholastic, 2012)
Tells the story of the Boston Tea Party of 1773 from the arrival of the ships full of controversial taxed tea in Boston Harbor, through the explosive protest meetings at the Old South Church, to the defiant act of dumping 226 chests of fine tea into the harbor on December 16.
b
Keywords: Boston Tea Party, Boston, Mass., 1773 -- Juvenile literature